Development of high-tech gas production: new knowledge, modern technologies and flexible procedures for indicative planning - V. А. Kryukov; А. N. Тоkаrеv; Е. А. Dubovitskaya (Georesursy, 2024)
Russia has the largest natural gas resource base. At the same time, a significant part of the gas reserves are classified as hard-to-recover reserves (HRR), and its supply to the market (primarily by pipeline transport) in modern conditions is associated with overcoming serious obstacles. Therefore, one of the key priorities for the development of the industry should be the production of high-tech gas – gas extracted from HRR or supplied to the market in the form of liquefied natural gas (LNG). Its production involves the use of both innovative technologies and new forms of coordination of participants in the processes of its production.Projects for the production of high-tech gas can be successfully implemented only if a number of restrictions are removed. Particularly noteworthy are: (1) technological problems, the solution of which requires the use of new types of equipment, materials and services; (2) organizational and economic problems associated with an increased level of costs.The authors' estimates show that the provision of additional tax preferences for the development of hard-to-recover gas – Achimov and Jurassic deposits – allows projects for their development to reach the level of profitability required by investors. At the same time, the state's tax revenues will be at the level of income received from the production of a similar volume of Cenomanian gas. This effect is associated with the mandatory inclusion of gas condensate in the composition of target products. In turn, when implementing LNG projects, even in the case of tax preferences, the state's revenues are no lower than with the existing taxation of gas production and its supply by pipeline transport. This circumstance is due to the fact that LNG-projects are characterized by higher capital intensity and greater flexibility in the directions of supply and subsequent use of liquefied gas.It is shown that in order to increase the extraction and production of high-tech gas, an important role is played by the formation of conditions for the accelerated development of related industries, primarily oil and gas field services and mechanical engineering, which can only be ensured through close cooperation between the participants using indicative planning mechanisms.